Simultaneous thermal analysis of cationic, nonionic and anionic polyacrylamide. Issue 12 (December 2019) - Steudel, Annett; Friedrich, Frank; Lieske, Wolfgang; Baille, Wiebke; König, Diethard; Schuhmann, Rainer; Emmerich, Katja
Abstract: Polyacrylamide (PAM) and its derivatives are the most commercially available water-soluble polymers and are frequently used for the production of clay-polymer composites. The characterization of their thermal behavior and decomposition was carried out mainly under reduced conditions by using N2, He or Ar gas flow. The object of this study was to investigate the thermal decomposition of cationic (PAMS, τ40 Cl), nonionic (PAM°S ), and anionic (NaPAMS, τ40 ) polyacrylamide under synthetic air (SynA) in detail using a thermogravimetry/differential scanning calorimetry (TG/DSC) system connected to a quadrupole mass spectrometer (MS). MS data indicated the release of NH3, CH4 and NO together with H2 O, CO2 and NO2 during decomposition. The gas release differed between the three polymers. Stoichiometric calculations showed that PAMS, τ40 Cl and PAM°S decomposed completely, while NaPAMS, τ40 decomposed only partially and the Na present for charge balancing remained in the form of Na2 O. The thermal decomposition of PAMS, τ40 Cl, PAM°S and NaPAMS, τ40 under SynA occurred via pyrolysis and oxidation reactions. Abstract : Materials science; Analytical chemistry; Organic chemistry; Agricultural soil science; Soil science; Mineralogy; Thermal analysis; Polyacrylamide; Evolved gas analysis